2020
DOI: 10.22271/chemi.2020.v8.i1s.8449
|View full text |Cite
|
Sign up to set email alerts
|

Integrated nutrient management of mustard (<em>Brassica juncea</em> L.) alluvial soil of Uttar Pradesh

Abstract: A field experiment was carried out in the pot culture of Soil Science and Agricultural Chemistry, C S Azad University of Agriculture & Technology during 2017-18. The experiment consisted 9 treatments viz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…Higher gross returns, net returns and benefit-cost ratio were obtained by the way of lesser cost of cultivation and also due to lower cost of organic manures viz., FYM compared to inorganic fertilizers and good market price of mustard. These findings were in confirmation with Maurya et al [28], Ranjan et al [16], Saha et al [25] and Kumawat et al [29].…”
Section: Economicssupporting
confidence: 88%
“…Higher gross returns, net returns and benefit-cost ratio were obtained by the way of lesser cost of cultivation and also due to lower cost of organic manures viz., FYM compared to inorganic fertilizers and good market price of mustard. These findings were in confirmation with Maurya et al [28], Ranjan et al [16], Saha et al [25] and Kumawat et al [29].…”
Section: Economicssupporting
confidence: 88%
“…Fatahi et al (2014) also found an increase in the number of leaves of Cowpea by the application of organic fertilizers such as compost, cow manure, and chicken manure. This finding is supported by Maurya et al (2020), who also observed the highest number of leaves on Mustard with the application of FYM. Adhikari et al (2023) reported that the application of Black Wonder increased the number of leaves on cabbage.…”
Section: Number Of Leaves Per Plantsupporting
confidence: 60%